B416 Two-year analysis of continuous spinal anaesthesia: a safe and "go with the flow" technique in high-risk patients. (11th August 2022) - Gonçalves Cardoso, R; Sepúlveda, D; Fonseca, R; Balão, J; Magalhães, J
Abstract : Background and Aims: There is a growing number of elderly patients with severe comorbidities requiring surgery. Continuous spinal anaesthesia (CSA) is an old technique that allows titration of local anesthetic (LA). Methods: Data from CSA in 2020–2021 was retrospectively reviewed. A total of 34 patients received CSA using a standard 18-G epidural catheter, removed at the end of surgery. Statistical analysis was performed using IBM SPSS® Statistics, 26. The study was approved by local institutional ethics committee. Results: Out of 34 patients, 53% were females. Median patient's age was 87 ± 6. Cardiovascular disease was the most common comorbidity ( Table 1 ). The most common procedure was orthopaedic hip surgery ( Table 2 ). Median surgery duration was 80 ± 41 min. Total dose of LA ranged between 1, 9 and 8, 0 mg (5, 5 ± 1, 5) and intrathecal opioid was used in 62% (fentanyl 10–25 µg or sufentanil 1, 5–2 µg) - Table 3 . Hypotension was the most common complication (38%). No major intraoperative complications were observed. There were no reports of postdural puncture headache, neurological deficits, or infection during hospitalization. Conclusions: CSA remains a reliable and safe anaesthetic technique, particularly in very frail patients with cardiac diseases. It allows the use of fractionated doses of LA until the desired surgical sensory blockade is achieved, minimizing the risk of severe hypotension. Additionally, with an intrathecal catheter in place, it is possible to extend the anaesthesia duration as needed. Thus, CSA still have a place in modern anaesthesia, particularly in high-risk patients proposed to long-lasting surgeries.